Bioactive Coatings for Implantable Devices (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Implantable materials are becoming increasingly important as an alternative for repairing, assisting, or replacing defective parts of the body, such as dental, orthopedic, and cardiac implants. This reprint focuses on research regarding modern technologies that enable various surface modifications, including coating with ceramics and polymers, and growth factors to improve their biocompatibility, antibacterial activity, and antithrombogenic properties or to promote the differentiation of cells.